Book Reviews/Compte rendu de livres (Contemporary Accounting Research, 1987)
Book reviewed in this article: R.H. Crandall and J.W. Cohrs. Intermediate Accounting: An Analytical Approach G.A. Welsch, C.T. Zlatkovich, W.T. Harrison, M. Nelson and M. Zin, Intermediate Accounting D.A. Leslie, Materiality: The Concept and its Application to Auditing D.L. Jensen, Editor, Information Systems in Accounting Education S.C.W. Salvary, Accounting: A Library of Quantifications H.M. Armitage, Linking Management Accounting Systems with Computer Technology J.E. Cooke and B.R. Dobing, Management Control of Computer‐Related Errors V. Salyzyn, The Economic Analysis of Taxes